Інформаційно-аналітична діяльність обласних наукових бібліотек - Зубова, Катерина; Сілютіна, Ірина (Видавництво Львівської політехніки, 2014)
The informational and analytical activities of research libraries are described. It is found out the most common types of information products created by regional research libraries.
Keywords: бібліотеки; інформаційні послуги; інформаційні продукти; інформаційна продукція; інформаційно-аналітична діяльність